2017
DOI: 10.18203/2320-6012.ijrms20173993
|View full text |Cite
|
Sign up to set email alerts
|

Post phototherapy bilirubin rebound: incidence and risk factors

Abstract: Background: Rebound hyperbilirubinemia may occur after cessation of phototherapy in new-borns in certain high-risk situations. However, data regarding the phenomenon of bilirubin rebound is lacking from India. Aim was to study the incidence and associated risk factors of post phototherapy rebound hyperbilirubinemia.Methods: The study subjects included all neonates (gestation >34 weeks) admitted to newborn unit who required phototherapy for hyperbilirubinemia. Unit protocol based on American academy of pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 5 publications
(12 reference statements)
3
11
0
Order By: Relevance
“…Diamond LK et al [10] , proposed a hypothesis for greater susceptibility to infection in male neonates due to factors responsible for defective immunoglobulin synthesis, which is located on "X" chromosome. These results were comparable with Arakhita Swain et al, [11] and Richa Soni et al, [12] as these studies also show male predominance. Arakhita Swain et al, [11] studied 126 neonates out of them 70 were male and 56 were female with sex ratio 1.25: 1; they found that 9% of female and 12.9% of male neonates developed SBR.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Diamond LK et al [10] , proposed a hypothesis for greater susceptibility to infection in male neonates due to factors responsible for defective immunoglobulin synthesis, which is located on "X" chromosome. These results were comparable with Arakhita Swain et al, [11] and Richa Soni et al, [12] as these studies also show male predominance. Arakhita Swain et al, [11] studied 126 neonates out of them 70 were male and 56 were female with sex ratio 1.25: 1; they found that 9% of female and 12.9% of male neonates developed SBR.…”
Section: Resultssupporting
confidence: 90%
“…In our study it was found that SBR was observed mainly in presence of risk factors. Similar observation were made by Al-Saedi et al, [16], Arakhita Swain et al, [11] and Richa soni et al, [12].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations